Insights from the current global financial crisis. - Heng Siam-Heng, (Universiti Kebangsaan Malaysia, 2008)
The best test of a theory is its actual performance in the real world, i.e. its practice. To quote Kurt Lewin, “There is nothing more practical than a good theory” The Wall Street has enjoyed the reputation as the bastion of lightly regulated financial industry. It is thus not surprising that as a result of the ongoing financial crisis, the USA is losing its economic clout and its intellectual authority in economic matters (Beddoes 2008). The crisis represents an occasion for social scientists to do some hard rethinking. It re-affirms the relevance of development studies. It also shows the wisdom displayed by the editors of this journal in taking the initiative two years ago to open a forum for development studies. This paper is a very modest contribution to the debate, by looking at some salient features of the ongoing financial crisis. As I observe elsewhere, economic development should be seen as part of societal development (Heng 2008). Economic development takes place within a historical context, within a concrete physical environment and societal conditions. Economic development can damage and even destroy the natural environment or our physical resources, e.g. a lush forest turned into a wasteland or semi-desert. Similarly, it can also damage or destroy societal resources, e.g. rampant corruption displacing public spirit among civil servants and politicians.